2021
DOI: 10.1177/00420980211040409
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and social disparities in the decline of activities during the COVID-19 lockdown in Greater London

Abstract: We use data on human mobility obtained from mobile applications to explore the activity patterns in the neighbourhoods of Greater London as they emerged from the first wave of COVID-19 lockdown restrictions during summer 2020 and analyse how the lockdown guidelines have exposed the socio-spatial fragmentation between urban communities. The location data are spatially aggregated to 1 km2 grids and cross-checked against publicly available mobility metrics (e.g. Google COVID-19 Community Report, Apple Mobility Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…The densest area of Madrid, the historic city centre, was less affected by disease than the inner suburbs ( Menéndez and Higueras García, 2020 ). However, socio-economic factors like overcrowding ( Gómez Giménez, 2020 ), and a large proportion of ‘essential workers’ who reported to their workplaces even during the lockdown, could have facilitated the spread of the virus ( Glodeanu et al, 2021 ), as was observed in other cities ( Trasberg and Cheshire, 2021 ).…”
Section: The Development Of Vulnerable Inner Suburbs and The Impact O...mentioning
confidence: 99%
“…The densest area of Madrid, the historic city centre, was less affected by disease than the inner suburbs ( Menéndez and Higueras García, 2020 ). However, socio-economic factors like overcrowding ( Gómez Giménez, 2020 ), and a large proportion of ‘essential workers’ who reported to their workplaces even during the lockdown, could have facilitated the spread of the virus ( Glodeanu et al, 2021 ), as was observed in other cities ( Trasberg and Cheshire, 2021 ).…”
Section: The Development Of Vulnerable Inner Suburbs and The Impact O...mentioning
confidence: 99%
“…Overall, the re-increase in activities after the COVID-19 lockdowns has been a mixed experience. For some, it has been a chance to return to normalcy, while for others, it has been a source of anxiety and worry [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…A large body of research is emerging that uses mobility data obtained from mobile phone applications to investigate human behaviour during the COVID-19 pandemic, notably changes in human mobility and internal migration (Kang et al, 2020), and the compliance of social distancing measures (Oliver et al, 2020). In addition, such data has been used to monitor the performance of consumption spaces and the wider retail sector during the pandemic (Trasberg & Cheshire, 2021;Ballantyne et al, 2021;Ballantyne et al, 2022).…”
Section: Measuring Retail Centre Performancementioning
confidence: 99%
“…Location data from smartphones face similar challenges to other consumer datasets in that they are often unrepresentative of particular social groups (e.g. generational biases), or of particular areas due to differences in access to mobile devices/internet (Trasberg & Cheshire, 2021;Parsons, 2020). In addition, such data often faces significant temporal limitations, depending on the sample of devices and applications used to collect it, and their representativeness of the general population (Gibbs et al, 2021).…”
Section: Measuring Retail Centre Performancementioning
confidence: 99%
See 1 more Smart Citation